What Drives the Cross‐Section of Credit Spreads?: A Variance Decomposition Approach - NOZAWA, YOSHIO (Journal of Finance, 2017)
ABSTRACT I decompose the variation of credit spreads for corporate bonds into changing expected returns and changing expectation of credit losses. Using a log‐linearized pricing identity and a vector autoregression applied to microlevel data from 1973 to 2011, I find that expected returns contribute to the cross‐sectional variance of credit spreads nearly as much as expected credit loss does. However, most of the time‐series variation in credit spreads for the market portfolio corresponds to risk premiums.